Cultivation of human values among gifted students through the implementation of the spiritual circle module in efforts of humanizing digital learning: a case study - Premanarayani Menon; Suganty Kanapathy; Isaac Sharvindran; Ong, Sy Ing; Deveendra (Penerbit Universiti Kebangsaan Malaysia, 2023)
The COVID-19 pandemic has changed the education system with the distinctive rise of e-learning. A sudden shift away from the physical classroom resulted in significant learning loss for students both academically and in their social-emotional progress. Also, the unwillingness of students to engage in virtual classrooms due to low self-esteem, lack of motivation, and self-appreciation has resulted in poor academic achievement. This phenomenon calls for the need to cultivate human values in the virtual classroom that helps to foster character building thus contributing to academic excellence. Thus, in this research, we aim to study the impact of the cultivation of human values in virtual classrooms and how it helps improve the teaching-learning environment through implementing the spiritual circle module. A total of 111 students participated in this study. The study used 21 close-ended questions assessed using a 5-point Likert scale. The study employed descriptive and inferential analyses using SPSS. The analysis revealed that the majority of the students agreed that the spiritual circle module has helped them to engage effectively in the classroom as well as contributed to their personal growth. Also, the Spearman correlation test revealed that there is a strong correlation between the cultivation of human values and student engagement and personal growth respectively. Hence, this study concludes that implementation of the spiritual circle module helps to humanize digital learning by fostering human values which contribute to the improvement of virtual class engagement and personal growth.